79.0k views
1 vote
(x - 2)(-5x2 + x) = (x)(-5x2)+(*)(x) + (-2)(-5x2)+(-2)(x) is an example of:

2 Answers

4 votes

Answer:

x=0 or x=1

Explanation:

(x−2)(−5x2+x)=x(−5x2)+x−2(−5x2)−2x

−5x3+11x2−2x=−5x3+10x2−x

Step 1: Add 5x^3 to both sides.

−5x3+11x2−2x+5x3=−5x3+10x2−x+5x3

11x2−2x=10x2−x

Step 2: Subtract 10x^2-x from both sides.

11x2−2x−(10x2−x)=10x2−x−(10x2−x)

x2−x=0

Step 3: Factor left side of equation.

x(x−1)=0

Step 4: Set factors equal to 0.

x=0 or x−1=0

x=0 or x=1

User Kizmar
by
4.6k points
4 votes

Answer: foil

Explanation:

User Dvcolgan
by
4.9k points